Erosion resistant explosion-proof wear-resistant castable for rkef ferronickel smelting rotary kiln
Patent Information
- Application Number
- CN202611225138.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明的目的在于针对现有RKEF镍铁冶炼回转窑用浇注料抗渣侵蚀能力不足、致密度偏低、高温性能不佳及升温过程易爆裂的技术问题,提供一种基于镁铝尖晶石的RKEF镍铁冶炼回转窑抗侵蚀防爆耐磨浇注料及其制备方法
(1)致密度与耐磨性能显著提升。利用镁铝尖晶石质骨料与高铝骨料的协同匹配,并以安德森模型设计颗粒级配,使整体颗粒分布接近连续曲线,减少孔隙堆积空隙率,形成高致密的骨架结构,使浇注料在回转窑强冲刷工况下的耐磨体积损失明显降低。磨损体积可降至≤3.0cm³,较常规材料(约6.0cm3)降低50%。
Smart Images

Figure CN122977831A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic non-metallic refractory materials technology, specifically relating to a castable based on magnesium aluminum spinel for use as a rotary kiln lining in the nickel-iron smelting process of a rotary kiln submerged arc furnace, and more specifically, relating to a castable with anti-corrosion, anti-cracking and wear-resistant properties and its preparation method. Background Technology
[0002] The rotary kiln electric furnace (RKEF) process is currently the mainstream technology for producing nickel-iron alloys from laterite nickel ore worldwide, accounting for more than two-thirds of the global nickel-iron production capacity. As one of the core pieces of equipment in this process, the rotary kiln is responsible for drying, preheating, and pre-reducing the laterite nickel ore. The high-temperature section inside the kiln can reach temperatures of 1400–1500°C, and the material is in a semi-molten state under a reducing atmosphere, creating extremely harsh service conditions for the lining material. Specifically, the rotary kiln lining is mainly subjected to multiple destructive effects during operation, including chemical erosion from high-temperature molten slag, mechanical wear from the material, severe thermal shock, and mechanical stress generated by the rotation of the kiln. Among them, the slag produced during the smelting of laterite nickel ore has high basicity, low viscosity, and strong fluidity, which has strong permeability and corrosiveness to the lining material. It is easy to react chemically with the components in the refractory material, leading to the destruction of the material structure and the deterioration of its performance. At the same time, a large amount of mineral powder and semi-molten material in the kiln continuously scours and rubs the lining surface during the kiln rotation, causing the material to wear and thin continuously. In addition, the frequent start-up and shutdown of the rotary kiln and the fluctuation of the temperature field in the kiln cause the lining material to be repeatedly subjected to alternating hot and cold thermal shocks, which easily generate thermal stress cracks and gradually expand.
[0003] Currently, the refractory materials and configuration schemes used in nickel-iron rotary kilns basically follow those of cement rotary kilns. The lining is mainly constructed using either refractory brick masonry or monolithic castable refractory. While refractory brick masonry is still used in certain specific areas, it has several insurmountable drawbacks: the brick joints are weak points in the lining structure, allowing high-temperature molten slag and hot air to easily seep in, leading to brick loosening, slippage, brick loss, and even complete ring collapse; irregularly shaped areas require custom-made bricks, resulting in high costs and long construction periods; and the construction cycle is also long, requiring 20-30 days for the brick lining of a single large rotary kiln, with complex procedures. While monolithic castable refractory has improved the integrity of the lining to some extent, existing castable products still have many shortcomings.
[0004] To address the aforementioned issues, those skilled in the art have conducted extensive research and improvements. For example, Chinese patent CN110330347A discloses a kiln lining material for the high-temperature zone of a nickel-iron rotary kiln. Its raw materials include 40-45 wt% mullite aggregate, 5-10 wt% corundum aggregate, 3-8 wt% corundum powder, 20-25 wt% mullite powder, 3-8 wt% silicon carbide powder, 3-8 wt% kyanite powder, 1-2 wt% steel fiber, 0.2-0.4 wt% explosion-proof fiber, 4-6 wt% pure calcium aluminate cement, and 4-6 wt% silica fume. While this material primarily uses mullite and corundum, and explosion-proof and steel fibers are added, its particle size distribution has not been systematically optimized using a mathematical model. The packing density between the aggregate and matrix has room for improvement, and magnesium aluminum spinel is not used as the main aggregate, resulting in limited resistance to high-temperature erosion from nickel-iron slag. For example, Chinese patent CN113754415A discloses a composite bonded nickel-iron rotary kiln castable, which uses a composite bonding method of high-alumina cement and liquid silica sol. Its raw materials include 60-65% bauxite particles, 20-27% fine bauxite powder, 3-6% silica fume, 1-4% high-alumina cement, 2-5% expansion agent, 0.1-0.5% explosion-proof agent, 1-3% steel fiber, 0.1-0.5% water-reducing agent, and 8-12% liquid silica sol. This castable is based on bauxite as the main system and does not use magnesium-aluminum spinel aggregate. The particle size distribution is not precisely designed using a mathematical model, and the CaO content is not strictly controlled. The generation of low-melting phase at high temperatures may affect the high-temperature performance of the material. For example, Chinese patent CN104150926A discloses a method for preparing a special castable refractory for the discharge port of a nickel-iron rotary kiln. It is composed of 40-80% bauxite or corundum aggregate, 5-20% fused mullite or fine corundum powder, 3-10% alumina powder, 3-10% silica powder, 1-8% pure calcium aluminate cement, and 3-30% calcium zirconate or zircon. This castable refractory is mainly designed for the discharge port area and does not address the overall performance optimization of the entire rotary kiln section. Furthermore, it does not utilize a magnesium-aluminum spinel aggregate system. In addition, existing technologies include methods for constructing specific areas of the rotary kiln using magnesium-aluminum-iron spinel bricks. However, this bricklaying method inherently suffers from numerous joints and poor overall integrity, making it impossible to achieve integrated molding of the lining.
[0005] In summary, existing castables for nickel-iron rotary kilns suffer from the following technical deficiencies: The main aggregate system, primarily composed of bauxite, mullite, or corundum, lacks sufficient resistance to high-temperature chemical erosion from nickel-iron slag, leading to erosion penetration and structural loosening after long-term operation; the particle size distribution lacks systematic mathematical model optimization, resulting in insufficient compaction of coarse and fine particles, limiting material density and wear resistance; the high CaO content in the bonding system easily generates low-melting-point phases at high temperatures, impairing the material's high-temperature structural strength and thermal shock resistance; explosion-proof measures rely mainly on explosion-proof fibers alone, lacking systematic coordination with particle size distribution and moisture control, leaving a risk of cracking during the heating and baking process; and a systematic material solution tailored to the specific operating conditions of the entire rotary kiln section has not been developed. Therefore, developing a castable with high density, strong wear resistance, excellent slag erosion resistance, good venting capacity and anti-cracking properties, and adaptability to the thermal shock and mechanical erosion of rotary kilns in submerged arc furnace processes is a pressing technical problem to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to address the technical problems of insufficient slag erosion resistance, low density, poor high-temperature performance, and easy cracking during the heating process in existing RKEF nickel-iron smelting rotary kiln castables. This invention provides an anti-erosion, explosion-proof, and wear-resistant castable for RKEF nickel-iron smelting rotary kilns based on magnesium aluminum spinel and its preparation method. This invention uses magnesium aluminum spinel as the main aggregate to improve slag erosion resistance, precisely designs the particle size distribution (q=0.22~0.28) using the Anderson model to improve density and wear resistance, adopts a low-cement, low-CaO bonding system combined with optimized aluminum-silicon ratio to improve high-temperature performance, and eliminates the risk of cracking through the systematic combination of organic explosion-proof fibers with particle size distribution and moisture control. This achieves a comprehensive improvement in the overall performance of the castable and effectively extends the service life of the rotary kiln lining.
[0007] To achieve the above objectives, the first technical objective of this invention is to provide an anti-corrosion, explosion-proof, and wear-resistant castable for RKEF nickel-iron smelting rotary kilns, the raw materials of which, by weight, include: 55-65 parts of magnesium-aluminum spinel aggregate; 15-20 parts of high-alumina aggregate; 25-40 parts of fine aluminum-silica powder; 3-8 parts of ultrafine active powder; 2-6 parts of low-cement composite binder; 0.05–0.3 parts of organic explosion-proof fiber; 1-3 parts steel fiber; Water-reducing agent (sodium tripolyphosphate) 0.1-0.6 parts; Add 4 to 5 parts water.
[0008] The magnesium-aluminum spinel aggregate is the main aggregate.
[0009] The particle size distribution of the castable was designed using the Anderson model, and the Anderson equation is: Ci =( di / dmax ) q The model is calculated as ×100%, where dmax = 15 mm, dmin = 0.2 μm, and the distribution coefficient q = 0.22–0.28. dmin is taken as 0.2 μm, corresponding to the minimum particle size of α-Al₂O₃ ultrafine powder. This model is used to determine the proportion of three particle sizes in magnesium-aluminum spinel aggregate. Aluminosilicate fine powder and ultrafine active powder are added as fillers based on this aggregate gradation, further approximating the Anderson curve with dmin = 0.2 μm for the overall powder system.
[0010] Calculations showed that when coarse (8–15 mm), medium (3–8 mm), and fine (1–3 mm) particles of magnesium-aluminum spinel aggregate were mixed in a ratio of 28:35:37, and then 28 parts of aluminosilicate fine powder (0.045–0.074 mm) and 5 parts of α-Al₂O₃ ultrafine powder (0.2–2 μm) were added, the correlation coefficient R between the cumulative particle size distribution of the overall particle system and the Anderson curve (d min = 0.2 μm, q = 0.26) was calculated. 2 The value ≥0.93 verifies that the gradation scheme can still effectively approximate the Anderson curve under the overall synergistic effect of aggregate and fine powder.
[0011] Taking q=0.26 as an example, the specific proportions are calculated as follows: Magnesium aluminum spinel aggregate was sieved into three particle sizes: fine (1–3 mm), medium (3–8 mm), and coarse (8–15 mm). Let the mass fractions of coarse, medium, and fine particles be x, y, and z (x + y + z = 100%), respectively, such that the cumulative passing rate C(d) of the mixed aggregate at sieve aperture size d satisfies Anderson's equation C(d) = (d / 15)^0.26 × 100.
[0012] Calculations showed that when the aggregate composition consisted of 28 parts coarse (8–15 mm), 35 parts medium (3–8 mm), and 37 parts fine (1–3 mm), the correlation coefficient R between the cumulative particle size distribution of the mixed aggregate and the Anderson curve was [value missing]. 2 ≥0.95.
[0013] Based on this, aluminum-silicon fine powder (0.045-0.074 mm) and ultrafine active powder (0.2-2 μm) are added to make the overall powder system further approach the Anderson curve with d min=0.2 μm.
[0014] Preferably, the particle size of the magnesium-aluminum spinel aggregate is 1-15 mm; the particle size of the high-alumina aggregate is 1-8 mm, and the Al2O3 content is ≥75%; the aluminosilicate fine powder is a mixture of 0.074-0.045 mm calcined bauxite fine powder and silica powder, wherein the weight ratio of calcined bauxite fine powder to silica powder is 4:1-8:1; the ultrafine active powder is α-Al2O3 with a particle size of 0.2-2 μm, and the median particle size D50 is controlled between 0.8-1.2 μm.
[0015] Preferably, the low-cement composite binder is a mixture of calcium aluminate cement and activated alumina, with a CaO content ≤1.0%, which can generate a highly stable refractory phase structure at 1100~1500℃.
[0016] Preferably, the organic explosion-proof fiber is thermoplastic polyurethane (TPU) fiber with a melting temperature <102℃, a diameter of 40μm, and a length of 2.5mm, forming an exhaust channel after melting in the initial stage of heating; the steel fiber is heat-resistant stainless steel fiber with a length of 25mm, and its chemical composition by mass percentage is: C 0.24%, Si 1.12%, Mn 0.96%, Ni 8.12%, Cr 18.26%, with the balance being Fe and unavoidable impurities.
[0017] Preferably, the aluminum-silicon ratio (mass ratio of Al2O3 to SiO2) of the castable is controlled within the range of 4.5:1 to 7:1, which can generate a stable combination of mullite and spinel phases at high temperature; the Al2O3 content of the castable is ≥78%.
[0018] The second technical objective of this invention is to provide a method for preparing the above-mentioned castable, comprising the following steps: S1: Add the specified proportions of magnesium-aluminum spinel aggregate, high-alumina aggregate, aluminosilicate fine powder, ultrafine active powder, and low-cement composite binder into a mixer and mix vigorously for 8-15 minutes to obtain a dry mix.
[0019] Preferably, in S1, the fine powder dispersion is insufficient when the dry mixing time is less than 8 minutes; when the dry mixing time exceeds 15 minutes, the particle breakage rate increases significantly. Under the condition of low cement composite binder, a dry mixing time of 8 to 15 minutes is sufficient to achieve uniform dispersion of fine powder, while the particle breakage rate can be controlled within an acceptable range.
[0020] S2: Add steel fibers to the dry mixture prepared in step S1, and mix at a low speed of 20-33 r / min for 2-3 minutes to ensure that the steel fibers are evenly dispersed in the dry mixture.
[0021] S3: During on-site construction, add the required amount of water to the mixture prepared in step S2, along with organic explosion-proof fibers and water-reducing agents, and stir for 5-8 minutes to obtain the grout.
[0022] Preferably, if the wet mixing time in S3 is less than 5 minutes, the water-reducing agent cannot play its full role; if it is greater than 8 minutes, the steel fibers will be unevenly distributed or the surface coating will peel off.
[0023] S4: Cast the slurry obtained in step S3 into a mold, cure for 24–48 hours, allow to air dry for 48–72 hours, and then heat to the working temperature at a rate of 20–30℃ / h. The endpoint of the air drying is when the moisture content of the castable is ≤1.5%. In humid environments, the drying time should be appropriately extended or forced ventilation should be used.
[0024] Preferably, the heating rate is 20-25°C / h, which can prevent water vapor from bursting due to excessively rapid heating.
[0025] Preferably, the curing temperature is 20–30℃. When the ambient temperature is below 20℃, the curing time should be extended appropriately or insulation measures should be taken; when the ambient temperature is above 30℃, attention should be paid to covering and moisturizing to prevent the surface from drying and cracking too quickly.
[0026] Furthermore, the present invention also provides the application of the above-mentioned castable as a lining material in the RKEF nickel-iron smelting rotary kiln.
[0027] The technical solution provided by this invention has the following beneficial effects: (1) Significantly improved density and wear resistance. By utilizing the synergistic matching of magnesium-aluminum spinel aggregate and high-alumina aggregate, and designing the particle size distribution using the Anderson model, the overall particle distribution approaches a continuous curve, reducing porosity and forming a highly dense skeleton structure. This significantly reduces the wear volume loss of the castable under the strong scouring conditions of a rotary kiln. The wear volume can be reduced to ≤3.0 cm³, compared to conventional materials (approximately 6.0 cm³). 3 (Reduced by 50%)
[0028] (2) Enhanced resistance to slag erosion. The magnesium aluminum spinel aggregate and the mullite phase in the aluminum silicate fine powder jointly construct a stable high-temperature phase structure. Combined with the low-caO (≤1.0%) low cement system, it significantly reduces the reactivity between slag and matrix, and shows higher resistance to chemical erosion of nickel-iron smelting slag. It can effectively inhibit slag penetration and structural loosening.
[0029] (3) Improved high-temperature structural strength and thermal shock stability. The low-cement composite binder reduces the CaO content and generates more stable high-temperature phases in the microstructure, enabling the castable to maintain stronger structural stability under high-temperature loads and temperature fluctuations. The room temperature compressive strength (110℃×24h) is ≥125MPa, and the high-temperature compressive strength (1300℃×3h) is ≥125MPa, which is significantly improved compared with conventional materials (approximately 70~80MPa).
[0030] (4) Significantly improved explosion-proof performance. The organic explosion-proof fiber melts and disappears in the early stage of heating, forming a uniform and interconnected micro-venting channel, which effectively solves the problem of difficult venting in low cement system, significantly reduces the risk of explosion caused by water vapor pressure accumulation, and improves the material safety during the first heating process.
[0031] (5) Enhanced crack resistance and toughness. The reinforcing steel fibers are distributed throughout the matrix, which can effectively inhibit crack propagation and disperse stress concentration areas. The steel fibers and the dense skeleton work together to prevent the castable from developing through cracks under the mechanical impact, alternating load and thermal shock of the rotary kiln, thus maintaining the integrity of the lining.
[0032] (6) Good construction adaptability and high molding quality. Anderson's gradation design balances material flowability and particle packing stability. Combined with the optimized water addition range (4-5 parts), higher casting density and lower risk of bleeding can be achieved. Segregation, bleeding and voids are less likely to occur during construction, improving the overall molding quality of the structure.
[0033] (7) Significantly extended service life. Due to substantial improvements in wear resistance, slag erosion resistance, thermal shock stability, and anti-cracking performance, the lining can maintain structural stability for a longer period of time. Compared with traditional rotary kiln castables, the overall service life is extended, which can effectively extend the maintenance cycle and reduce operating costs. Attached Figure Description
[0034] Figure 1 This is a flowchart illustrating the preparation process of the RKEF nickel-iron smelting rotary kiln anti-erosion, explosion-proof, and wear-resistant castable of the present invention. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example 1: A castable refractory formulated with 60 parts magnesium-aluminum spinel aggregate and its preparation method.
[0036] This embodiment provides an RKEF nickel-iron smelting rotary kiln anti-corrosion, explosion-proof, and wear-resistant castable. By weight, its raw material composition is as follows: 60 parts magnesium-aluminum spinel aggregate; 18 parts high-alumina aggregate; 30 parts aluminosilicate fine powder; 5 parts ultrafine active powder; 4 parts low-cement binder; 2 parts steel fiber; 0.15 parts organic explosion-proof fiber; 0.3 parts sodium tripolyphosphate water-reducing agent; and 4.5 parts water. The aluminum-silicon ratio (mass ratio of Al2O3 to SiO2) of the castable in this embodiment is 5.1:1.
[0037] Its preparation method is as follows: S1: Add the specified amounts of magnesium-aluminum spinel aggregate, high-alumina aggregate, aluminosilicate fine powder, ultrafine active powder, and low-cement composite binder into the mixer at once, and mix vigorously for 12-15 minutes to obtain dry mix.
[0038] S2: Add heat-resistant stainless steel fibers (25mm in length) to the dry mixture prepared in step S1, and mix at low speed for 2 minutes to ensure that the steel fibers are evenly dispersed in the dry mixture.
[0039] S3: Add water, thermoplastic polyurethane fiber and sodium tripolyphosphate water-reducing agent in sequence to the mixture prepared in step S2, and wet mix for 6 minutes to obtain the casting slurry.
[0040] S4: Pour the slurry obtained in step S3 into the mold, compact it, and then cure it at room temperature for 36 hours, let it dry naturally for 60 hours, and then bake it at 1300℃ at a rate of 25℃ / h before putting it into use.
[0041] Testing revealed that the castable obtained in this embodiment exhibits a room temperature compressive strength (110℃×24h) ≥125MPa and a high temperature compressive strength (1300℃×3h) ≥125MPa; a room temperature flexural strength (110℃×24h) ≥18.5MPa and a high temperature flexural strength (1300℃×3h) ≥20MPa; and a wear volume ≤2.5cm². 3 ≥20 cycles of water-cooled thermal shock at 1100℃.
[0042] In this embodiment, the magnesium aluminum spinel aggregate content is 60 parts, combined with Anderson gradation (q=0.26) to achieve the densest overall particle packing, significantly reducing residual porosity between particles. This forms the structural basis for a room temperature compressive strength exceeding 125 MPa. Simultaneously, the total CaO content in the low-cement binder is ≤1.0%, reducing the formation of low-melting-point phases such as anorthite during 1300℃ firing, preventing high-temperature strength degradation, and ensuring a high-temperature compressive strength also exceeding 125 MPa. The venting channels formed by the melting of TPU fibers in the initial heating stage effectively prevent the accumulation of internal moisture pressure, ensuring no cracking during the furnace drying process. Example 2: Castable refractory formulated with 55 parts magnesium-aluminum spinel aggregate and its preparation method
[0043] This embodiment provides an RKEF nickel-iron smelting rotary kiln anti-corrosion, explosion-proof, and wear-resistant castable. By weight, its raw material composition is as follows: 55 parts magnesium aluminum spinel aggregate; 20 parts high alumina aggregate; 35 parts aluminosilicate fine powder; 4 parts ultrafine active powder; 5 parts low cement binder; 2.5 parts steel fiber; 0.2 parts organic explosion-proof fiber; 0.4 parts sodium tripolyphosphate water-reducing agent; and 4.8 parts water. The aluminum-silicon ratio (mass ratio of Al2O3 to SiO2) of the castable in this embodiment is 4.8:1.
[0044] Its preparation method is as follows: S1: Add the specified amounts of magnesium-aluminum spinel aggregate, high-alumina aggregate, aluminosilicate fine powder, ultrafine active powder, and low-cement composite binder into the mixer at once, and mix vigorously for 11-14 minutes to obtain dry mix.
[0045] S2: Add heat-resistant stainless steel fibers (25mm in length) to the dry mixture prepared in step S1, and mix at low speed for 2 minutes to ensure that the steel fibers are evenly dispersed in the dry mixture.
[0046] S3: Add water, thermoplastic polyurethane fiber and sodium tripolyphosphate water-reducing agent in sequence to the mixture prepared in step S2, and wet mix for 5 minutes to obtain the casting slurry.
[0047] S4: Cast the slurry obtained in step S3 into a mold, cure at room temperature for 48 hours, dry naturally for 72 hours, and then heat it to 1300℃ at 20-25℃ / h and keep it at that temperature for 6 hours before putting it into use.
[0048] Testing revealed that the castable obtained in this embodiment exhibits a room temperature compressive strength (110℃×24h) ≥130MPa and a high temperature compressive strength (1300℃×3h) ≥140MPa; a room temperature flexural strength (110℃×24h) ≥18.5MPa and a high temperature flexural strength (1300℃×3h) ≥20MPa; and a wear volume ≤3.0cm³. 3 The erosion loss is reduced by about 30% compared to ordinary low-cement castables; there is no cracking during the heating process. Example 3: A castable refractory formulated with 65 parts magnesium-aluminum spinel aggregate and its preparation method.
[0049] This embodiment provides an RKEF nickel-iron smelting rotary kiln anti-corrosion, explosion-proof, and wear-resistant castable. By weight, its raw material composition is as follows: 65 parts magnesium-aluminum spinel aggregate; 15 parts high-alumina aggregate; 28 parts aluminosilicate fine powder; 6 parts ultrafine active powder; 3 parts low-cement binder; 1.5 parts steel fiber; 0.1 parts organic explosion-proof fiber; 0.2 parts sodium tripolyphosphate water-reducing agent; and 4.2 parts water. The aluminum-silicon ratio (mass ratio of Al2O3 to SiO2) of the castable in this embodiment is 5.4:1.
[0050] Its preparation method is as follows: S1: Add the specified amounts of magnesium-aluminum spinel aggregate, high-alumina aggregate, aluminosilicate fine powder, ultrafine active powder, and low-cement composite binder into the mixer at once, and mix vigorously for 12-15 minutes to obtain dry mix.
[0051] S2: Add heat-resistant stainless steel fibers (25mm in length) to the dry mixture prepared in step S1, and mix at low speed for 3 minutes to ensure that the steel fibers are evenly dispersed in the dry mixture.
[0052] S3: Add water, thermoplastic polyurethane fiber and sodium tripolyphosphate water-reducing agent in sequence to the mixture prepared in step S2, and wet mix for 6-8 minutes to obtain the casting slurry.
[0053] S4: Vibrate the slurry obtained in step S3 to form a mold, cure for 24 hours, air dry for 48 hours, and then heat to 1300℃ at 30℃ / h to complete the oven drying.
[0054] Testing revealed that the castable obtained in this embodiment exhibits a room temperature compressive strength (110℃×24h) ≥125MPa and a high temperature compressive strength (1300℃×3h) ≥125MPa; a room temperature flexural strength (110℃×24h) ≥18.5MPa and a high temperature flexural strength (1300℃×3h) ≥20MPa; and a wear volume ≤3.0cm³. 3 Bulk density (110℃×24h) ≥2.70g / cm³ 3 Apparent porosity ≤15%; ≥25 cycles of water-cooled thermal shock at 1100℃. Comparative Example
[0055] A high-alumina, low-cement castable was prepared using 55 parts of high-alumina bauxite aggregate (1–8 mm), 30 parts of high-alumina bauxite fine powder (0.074–0.045 mm), 5 parts of silica fume, 5 parts of α-Al₂O₃ powder, 5 parts of calcium aluminate cement, 0.15 parts of polypropylene explosion-proof fiber, 2 parts of steel fiber, 0.3 parts of sodium tripolyphosphate water-reducing agent, and 4.5 parts of water. This comparative example did not use magnesium aluminum spinel aggregate; the particle size distribution was a traditional sieve gradation, not the Anderson model gradation, and the CaO content was approximately 1.8%.
[0056] Under the same raw material particle size, the same construction conditions, and the same testing conditions, comparative tests were conducted on the various embodiments of the present invention and the comparative example. The results showed that the castable obtained in this comparative example had a room temperature compressive strength (110℃×24h) of 70 MPa, a high temperature compressive strength (1300℃×3h) of 80 MPa, a room temperature flexural strength (110℃×24h) of 8 MPa, a high temperature flexural strength (1300℃×3h) of 10 MPa, and an abrasion volume of 6.0 cm³. 3 . Detection and Analysis
[0057] The castables prepared in Examples 1-3 and the conventional low-cement castables of the comparative example were subjected to performance tests and analyses under the same conditions. The test methods for each performance are as follows: (1) Compressive strength test: The test shall be conducted in accordance with GB / T 5072 "Test method for compressive strength of refractory materials at room temperature". The sample size is 230mm×114mm×65mm (or φ50mm×50mm). There shall be no less than 3 samples in each group. The loading rate is 0.5~1.0MPa / s. The room temperature compressive strength after drying at 110℃×24h and after firing at 1300℃×3h shall be tested respectively. The arithmetic mean shall be taken as the final result.
[0058] (2) Flexural strength test: The test was conducted according to GB / T 3001 "Test method for flexural strength of refractory materials at room temperature". The sample size was 230mm×114mm×65mm (or 160mm×40mm×40mm), the span was 100mm, and the loading rate was 0.15±0.05MPa / s. The flexural strength at room temperature was tested after drying at 110℃ for 24h and after firing at 1300℃ for 3h. The arithmetic mean was taken as the final result.
[0059] (3) Abrasion resistance test: The test was conducted according to GB / T 18301 "Test Method for Abrasion Resistance of Refractory Materials at Room Temperature". A sandblasting abrasion tester was used. The sample size was 50mm in diameter × 50mm. The abrasive was silicon carbide or corundum. The test was conducted under a pressure of 0.1 to 0.15 MPa, with the wear volume (cm³) as the test result. 3 As an evaluation index for wear resistance, the arithmetic mean is taken as the final result.
[0060] (4) Erosion resistance test: The erosion resistance was tested according to GB / T 18301-2012 "Test Method for Abrasion Resistance of Refractory Materials at Room Temperature". A sandblasting abrasion tester was used, with the wear volume (cm²) as the test result. 3 As an evaluation metric, the arithmetic mean is taken as the final result.
[0061] (5) Thermal shock resistance test: The test was conducted by water cooling thermal shock cycle test at 1100℃. The test was conducted according to GB / T 30873 "Test Method for Thermal Shock Resistance of Refractory Materials". The sample size was 230mm×114mm×65mm. The sample was placed in a heating furnace at 1100℃ and kept at that temperature for 30min. After being removed, it was quickly immersed in flowing cold water to cool for 3-5min. After being removed, it was allowed to dry naturally. The crack propagation, spalling and residual strength of the sample surface were observed. The number of cycles when cracks or spalling occurred was recorded. This number was used as the evaluation index of thermal shock resistance. The number of samples in each group was not less than 3. The arithmetic mean was taken as the final result.
[0062] Table 1 summarizes the formulation composition and main performance data of each embodiment and comparative example.
[0063] Table 1. Comparison of formulation composition and performance between each embodiment and the comparative example.
[0064] In summary, regarding compressive strength, the room temperature compressive strength (110℃×24h) of the various embodiments of the present invention is 125-130 MPa, and the high temperature compressive strength (1300℃×3h) is 125-140 MPa; the room temperature compressive strength of the comparative example is 70 MPa, and the high temperature compressive strength is 80 MPa. The compressive strength of the castable of the present invention is significantly improved compared to the comparative example, with an increase of approximately 79%-86% in room temperature compressive strength and approximately 56%-75% in high temperature compressive strength.
[0065] Regarding flexural strength, Example 1 exhibits a room-temperature flexural strength (110℃×24h) ≥18.5MPa and a high-temperature flexural strength (1300℃×3h) ≥20MPa; the comparative example shows a room-temperature flexural strength (110℃×24h) of 8MPa and a high-temperature flexural strength (1300℃×3h) of 10MPa. The flexural strength of the castable of this invention is significantly improved compared to the comparative example, with an increase of approximately 131% in room-temperature flexural strength and approximately 100% in high-temperature flexural strength. Regarding abrasion resistance, Example 1 shows a wear volume ≤2.5cm². 3 Comparative wear volume 6cm 3 The wear volume of the castable refractory of this invention is reduced by approximately 58% compared to the comparative example. Regarding thermal shock resistance, Example 1 exhibits ≥20 cycles of water-cooled thermal shock at 1100°C, and Example 3 exhibits ≥25 cycles of water-cooled thermal shock at 1100°C, demonstrating excellent thermal shock resistance. Regarding erosion resistance, the erosion loss of Example 2 is reduced by 30% compared to the comparative example.
[0066] Based on the above test and analysis results, the castables of the various embodiments of the present invention are significantly superior to the conventional low-cement castables in terms of compressive strength, flexural strength, wear resistance, erosion resistance and thermal shock resistance, and can effectively extend the service life of the RKEF nickel-iron smelting rotary kiln lining.
[0067] The above description is merely a specific embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A corrosion-resistant, explosion-proof, and wear-resistant castable for RKEF nickel-iron smelting rotary kilns, characterized in that, By weight, its raw materials include: 55-65 parts of magnesium-aluminum spinel aggregate; 15-20 parts of high-alumina aggregate; 25-40 parts of fine aluminum-silica powder; 3-8 parts of ultrafine active powder; 2-6 parts of low-cement composite binder; 0.05–0.3 parts of organic explosion-proof fiber; 1-3 parts steel fiber; Water-reducing agent: 0.1–0.6 parts; Add 4-5 parts water; The magnesium-aluminum spinel aggregate is the main aggregate. The magnesium-aluminum spinel aggregate consists of three particle size grades: 1–3 mm, 3–8 mm, and 8–15 mm. The 8–15 mm grade comprises 25–31 wt%, the 3–8 mm grade 32–38 wt%, and the 1–3 mm grade 34–40 wt%, with a total of 100 wt%. The cumulative particle size distribution of the magnesium-aluminum spinel aggregate satisfies the Anderson equation. Ci =( di / dmax )*q*×100%, where d_max=15mm, distribution coefficient q=0.22~0.28; and the cumulative particle size distribution of the overall particle system composed of magnesium aluminum spinel aggregate, aluminum silicon fine powder, and ultrafine active powder also satisfies the Anderson equation.
2. The castable refractory according to claim 1, characterized in that, The magnesium-aluminum spinel aggregate has a particle size of 1–15 mm; the high-alumina aggregate has a particle size of 1–8 mm and an Al2O3 content ≥75%; the aluminosilicate fine powder is a mixture of 0.074–0.045 mm calcined bauxite fine powder and silica powder, wherein the weight ratio of calcined bauxite fine powder to silica powder is 4:1–8:1; the ultrafine active powder is α-Al2O3 with a particle size of 0.2–2 μm and a median particle size D50 ≤1 μm.
3. The castable refractory according to claim 1, characterized in that, The composite binder is a mixture of calcium aluminate cement and activated alumina, with a weight ratio of calcium aluminate cement:activated alumina of 1:9 to 1:
10. The CaO content of the calcium aluminate cement is ≤5%, the CaO content of the activated alumina is ≤0.5%, and the total CaO content in the composite binder is ≤1.0%.
4. The castable refractory according to claim 1, characterized in that, The organic explosion-proof fiber is a thermoplastic polyurethane fiber with a melting temperature of <102℃. After melting in the initial stage of heating, it forms an exhaust channel.
5. The castable refractory according to claim 1, characterized in that, The aluminum-silicon ratio of the castable is controlled within the range of 4.5:1 to 7:
1.
6. The castable refractory according to claim 1, characterized in that, The Al2O3 content of the castable is ≥78%.
7. The castable refractory according to claim 1, characterized in that, The castable has a room temperature compressive strength (110℃×24h) ≥125MPa, a high temperature compressive strength (1300℃×3h) ≥125MPa, a room temperature flexural strength (110℃×24h) ≥18.5MPa, a high temperature flexural strength (1300℃×3h) ≥20MPa, and a wear volume ≤3.0cm³. 3 .
8. A method for preparing a castable refractory as described in any one of claims 1 to 7, characterized in that, Includes the following steps: S1: Add the specified proportions of magnesium aluminum spinel aggregate, high alumina aggregate, aluminosilicate fine powder, ultrafine active powder and low cement composite binder into the mixer and mix vigorously for 8 to 15 minutes to obtain dry mix. S2: Add steel fibers to the dry mixture prepared in step S1 and mix at low speed for 2-3 minutes to ensure that the steel fibers are evenly dispersed in the dry mixture; S3: Add the specified amount of water to the mixture prepared in step S2, along with organic explosion-proof fibers and water-reducing agent, and stir for 5-8 minutes to obtain the casting slurry; S4: Cast the slurry obtained in step S3 into a mold, cure for 24 to 48 hours, and let it dry naturally until the moisture content of the slurry is ≤1.5%. Then, raise the temperature to 1100 to 1500℃ at a rate of 20 to 30℃ / h.
9. The preparation method according to claim 8, characterized in that, The curing temperature in S4 is 20-30℃; when the ambient temperature is below 20℃, heat preservation measures are taken to maintain the temperature of the castable at 20-30℃; when the ambient temperature is above 30℃, covering and moisture retention measures are taken to maintain the temperature of the castable at 20-30℃.
Citation Information
Patent Citations
Preparation method for special casting material of ferronickel rotary kiln discharge opening
CN104150926A
Kiln liner material in high temperature area of ferronickel rotary kiln and production process thereof
CN110330347A
Composite combined ferronickel rotary kiln castable and preparation method thereof
CN113754415A